Biomechanical characteristics and speed adaptation during kick double poling on roller skis in elite cross-country skiers - Göpfert, C.; Holmberg, H. C.; Stöggl, T.; Müller, E.; Lindinger, S. J. (Sports Biomechanics, 2013)
Recent developments in cross-country ski racing should promote the use of kick double poling. This technique, however, has not been the focus in athletes' training and has barely been investigated. The aims of the present study were to develop a function-based phase definition and to analyse speed adaptation mechanisms for kick double poling in elite cross-country skiers. Joint kinematics and pole/plantar forces were recorded in 10 athletes while performing kick double poling at three submaximal roller skiing speeds. A speed increase was associated with increases in cycle length and rate, while absolute poling and leg push-off durations shortened. Despite maintained impulses of force, the peak and average pole/leg forces increased. During double poling and leg push-off, ranges of motion of elbow flexion and extension increased (p < 0.05) and were maintained for hip/knee flexion and extension. Cycle length increase was correlated to increases in average poling force (r = 0.71) and arm swing time (r = 0.88; both p < 0.05). The main speed adaptation was achieved by changes in double poling technique; however, leg push-off showed high variability among elite skiers, thus illustrating important aspects for technique training.